2017
DOI: 10.1371/journal.pgen.1007088
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Caenorhabditis elegans pocket protein LIN-35 reveals MuvB's innate function as the repressor of DREAM target genes

Abstract: The DREAM (Dp/Retinoblastoma(Rb)-like/E2F/MuvB) transcriptional repressor complex acts as a gatekeeper of the mammalian cell cycle by establishing and maintaining cellular quiescence. How DREAM’s three functional components, the E2F-DP heterodimer, the Rb-like pocket protein, and the MuvB subcomplex, form and function at target gene promoters remains unknown. The current model invokes that the pocket protein links E2F-DP and MuvB and is essential for gene repression. We tested this model by assessing how the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
96
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(98 citation statements)
references
References 72 publications
2
96
0
Order By: Relevance
“…This dataset includes the interactions of 296 predicted transcription factors (Bass et al 2016) as prey screened to interact with 534 promoter loci bait sequences (Reece-Hoyes et al 2011). We found that 48 bait sequences in the Y1H dataset were known to be bound by the DREAM complex in their promoter region in late embryos (Goetsch et al 2017). We found that 123 of the 296 TFs showed binding to at least one of the 48 DREAM target promoter loci in the Y1H data set.…”
Section: Selection Of Transcription Factor Candidates For Rnai Screenmentioning
confidence: 70%
See 1 more Smart Citation
“…This dataset includes the interactions of 296 predicted transcription factors (Bass et al 2016) as prey screened to interact with 534 promoter loci bait sequences (Reece-Hoyes et al 2011). We found that 48 bait sequences in the Y1H dataset were known to be bound by the DREAM complex in their promoter region in late embryos (Goetsch et al 2017). We found that 123 of the 296 TFs showed binding to at least one of the 48 DREAM target promoter loci in the Y1H data set.…”
Section: Selection Of Transcription Factor Candidates For Rnai Screenmentioning
confidence: 70%
“…In C. elegans, the DREAM complex alters chromatin structure in the nucleus to transcriptionally repress germline genes in somatic cells (Costello and Petrella 2019;Cui et al 2006;Latorre et al 2015;Petrella et al 2011;Rechtsteiner et al 2019;Unhavaithaya et al 2002;Wang et al 2005;Wu et al 2012). The DREAM complex is completely conserved between mammals and C. elegans, and comprised of eight proteins: E2F-DP heterodimer (EFL-1 & DPL-1), a retinoblastoma-like pocket protein , and a 5-subunit MuvB complex (LIN-9, LIN-37, LIN-52, LIN-53, and the DNA binding subunit LIN-54) (Goetsch et al 2017;Harrison et al 2006;Latorre et al 2015;Sadasivam and DeCaprio 2013). In C. elegans, a mutant form of LIN-54 is incapable of binding the majority of DREAM complex target loci due to a change in a single amino acid in the DNA binding motif (Tabuchi et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…We tested the impact of this severing on the chromatin localization of DREAM components using chromatin immunoprecipitation (ChIP). We chose 4 genes, set-21, mis-12, polh-1, and air-1, as representative DREAM target genes; in lin-35 null embryos, the chromatin occupancy of DREAM components was greatly diminished at each of their gene promoters [17]. Importantly, DREAM component chromatin occupancy was undetectable at the air-1 promoter in the absence of LIN-35 [17].…”
Section: E2f-dp-lin-35 and Muvb Subcomplexes Independently Co-occupy mentioning
confidence: 99%
“…Like pRb, p130 and p107 interact with an E2F-DP transcription factor heterodimer [11][12][13]. Unlike pRb, they also interact with the highly conserved 5-subunit MuvB complex, forming the DREAM (for Dp, Rb-like, E2F, and MuvB) complex, which mediates transcriptional repression through MuvB [8,[14][15][16][17]. To address how the Rb-like pocket protein contributes to MuvB-mediated gene repression, we disrupted the interaction between the sole Caenorhabditis elegans pocket protein LIN-35 and the MuvB subunit LIN-52 using CRISPR/Cas9 targeted mutagenesis.…”
mentioning
confidence: 99%
“…Drosophila Myb also acts in opposition to the DREAM complex to regulate chorion gene amplification in ovarian follicle cells and programmed neuronal cell death 12,42,43 . Interestingly, recent studies in C. elegans have shown that the MuvB complex can effectively repress gene expression in the absence of the LIN-35 RB-family protein that was previously thought to be required for repression by DREAM complexes 44 . Although C. elegans and other nematode species contain two Myb-related genes that encode homologs of the CDC5/CEF1 splicing factor and the SNAPc small nuclear RNA transcription factor, they do not contain an animal-type Myb gene that might relieve repression by DREAM complexes 3 .…”
Section: Introductionmentioning
confidence: 99%